Impact of the Human Microbiome on Nephrolithiasis - Hae Do Jung; Joo Yong Lee (Urogenital Tract Infection, 2021)
Nephrolithiasis has many causes, and its prevalence is increasing worldwide. The interest in the human microbiome is growing because of the advance of new diagnostic techniques, and recent studies have suggested a link between the microbiome and nephrolithiasis. This paper reviewed the role of the microbiome in nephrolithiasis. The absence of Oxalobacter formigenes induces hyperoxaluria, which promotes calcium oxalate stone (CaOx) formation. Escherichia coli promote CaOx supersaturation through hypocitraturia caused by the bacterial production of citrate lyase. Infection stones are associated with urea-splitting organisms, particularly Proteus mirabilis, and the stones themselves contain many species of bacteria.